“Democratizing” Courts in an Authoritarian Polity? Using an Interest-Based Bargaining Theory to Explain China’s Pilot Reform on Its People’s Assessor System - Michelle Miao (Washington University Global Studies Law Review, 2021)
Can a jury-like institution be empowered to fully represent ordinary citizens under an authoritarian regime? This article evaluates the process and significance of China’s 2015-2018 pilot project to reform its people’s assessor regime. The reform, at least nominally, sought to empower citizenry in two main ways – to ensure that laypersons are randomly selected to represent the society in general as well as to safeguard their meaningful role during trials and deliberation. My findings demonstrate that this recent experimentation has failed to empower lay participation. This failure has its roots in the twin difficulties within China’s political- judicial bureaucracy: power-sharing and political control. I support these theoretical arguments with empirical evidence obtained through surveys with people’s assessors and interview responses of Chinese judges. Overall, I claim that the institution of people’s assessors provides a double dividend of efficiency and legitimacy to the state. The path of the reform has been decisively shaped by interest-based bargaining processes among stakeholders.
Keywords: authoritarianism; lay assessor; courts; jury; China